Development of Oral Thin Film Strip Contained Ethanol Extract of Clove Leaves (Syzygium aromaticum (L.) Merr. & Perry) - Bayu Eko Prasetyo; Mariadi; Emil Salim (Talenta Publisher, 2022)
Halitosis or bad breath can occur due to poor oral hygiene care, dental caries or infections in the oral cavity. The use of mouth fresheners is one of the solution product to overcome the problem. Oral Thin Film Strip (OTFS) is an alternative mouth freshener. The preparation of OTFS was carried out using the solvent casting method. Five film formula were made with varying concentrations of gelatin and HPMC, namely F1 (0:3), F2 (1:3), F3 (1:1), F4 (3:1), and F5 (3:0). Evaluation of the preparation included organoleptic test, weight uniformity, thickness, disintegration time, pH, and folding resistance. Stability testing was carried out for 3 months at 25±2°C and 40±2°C. Antibacterial activity test against Streptococcus mutans (S. mutans) on the preparation was done using disc diffusion method. The OTFS preparation produced gave a homogeneous colour, aroma and taste of the extract. The resulting preparation had weight between 0.345-0.180 grams, thickness between 0.148-0.247 mm, disintegration time of 44-60 seconds, a pH between 6.06-6.33, and a film folding resistance between 339.83-673.67 times. The preparation was stable in storage for 3 months at a temperature of 25±2℃ and 40±2℃. The preparation showed antibacterial activity against S. mutans with zone of inhibition between 8.0-9.1 mm. Clove leaf ethanol extract can be formulated into OTFS preparations with good physical characteristics, stable in 3 months storage and had antibacterial activity against S. mutans so that it has the potential to overcome bad breath.